PELATIHAN FIRST AID GEMPA DI SMA ISLAM AL-IKHWAN SESAIT KEC. KAYANGAN KLU LOMBOK UTARA 2019 - Putri Wulandini; Roni Saputra; Ainil Fitri; Lora Marlita (Universitas Lancang Kuning, 2019)
First aid and treatment for earthquake victims, First Aid where before getting help from doctors / paramedics. First aid is not a perfect treatment or treatment, but it involves temporary help done by a P3K officer (medical officer or lay person) who first sees the victim, which in this case is the young generation in Lombok. First aid actions carried out correctly will reduce disability or save and save victims from, but if first aid actions are done improperly, it can even worsen the result of an accident and even kill the victim. The purpose of this community service is to prepare a generation of teenagers who have the knowledge and skills in reporting emergency emergencies that may occur in schools and in the immediate vicinity of the earthquake. This community service is carried out at the Al-Ikhwan Sesait Islamic High School Kec. Kayangan Klu, North Lombok 2019. This Dedication Method is applied in the form of training with an initial method that is given lecture material, then demostrated using, after that students use one by one printed. The students are 100% able to practice how to give first aid to accidents and help stop cardiac arrest.